4DNvestigator: time series genomic data analysis toolbox. Issue 1 (1st January 2021) - Lindsly, Stephen; Chen, Can; Liu, Sijia; Ronquist, Scott; Dilworth, Samuel; Perlman, Michael; Rajapakse, Indika
ABSTRACT: Data on genome organization and output over time, or the 4D Nucleome (4DN), require synthesis for meaningful interpretation. Development of tools for the efficient integration of these data is needed, especially for the time dimension. We present the '4DNvestigator', a user-friendly network-based toolbox for the analysis of time series genome-wide genome structure (Hi-C) and gene expression (RNA-seq) data. Additionally, we provide methods to quantify network entropy, tensor entropy, and statistically significant changes in time series Hi-C data at different genomic scales.